Electroacupuncture alleviates surgery-induced cognitive dysfunction by increasing α7-nAChR expression and inhibiting inflammatory pathway in aged rats. (17th October 2017) - Liu, Pei-Rong; Zhou, Ying; Zhang, Yu; Diao, Shu
Highlights: Electroacupuncture (EA) improve cognitive dysfunction in POCD rats. Electroacupuncture increase hippocampal expression of α7-nAChR. Downregulation of TNFα and IL-1β may be related to activated α7-nAChR by EA. Abstract: Postoperative cognitive dysfunction (POCD) is a common disorder of cognitive functions in aged patients following anesthesia and surgery. α7-nicotinic acetylcholine receptors (α7-nAChR) plays a regulatory role in cognitive processes and is involved in cognitive deficits. This study aims to observe the effect of electroacupuncture (EA) on the cognitive function in aged POCD rats, and its regulation on expressions of hippocampal α7-nAChR and proinflammatory factors. Ninety healthy Sprague-Dawley male aged rats were randomly divided into three groups (each n = 30): control group (sham operation), model group (partial hepatectomy), and electroacupuncture (EA) group. The cognitive function was detected by Morris water-maze test, and the changes of hippocampal expressions of α7-nAChR, tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) were detected by immunohistochemical method. Our results showed that compared with the model group, the EA group had significantly shorter escape latency and decreased crossing platform times at 1d, 3d and 7d after operation (P < 0.05). α7-nAChR positive neurons in the hippocampus decreased and TNF-α and IL-1β positive neurons increased on postoperative days 1, 3 and 7. Compared with the model group, the α7-nAChR positive neurons were increased and TNF-α and IL-1β positive neurons were decreased in the EA group at the same time points (P < 0.05). In conclusion, the electroacupuncture regulation can improve the learning and memory abilities in POCD rats, and its mechanism may be related to upregulation of α7-nAChR and downregulation of TNF-α and IL-1β in hippocampus.